Effect of Butein, a Plant Polyphenol, on Apoptosis and Necroptosis of Prostate Cancer Cells in 2D and 3D Cultures - Yeji Lee; Changyeol Lee; Sang-Han Lee; Yoon-Jin Lee (Life, 2025)
Butein (3,4,2′,4′-tetrahydroxycalone) is a chalcone derivative and plant polyphenol extracted from Rhus verniciflua Stokes. Butein has an open C-ring structure and a variety of biological activities. Molecular mechanisms by which butein could affect cell viability, ROS levels, mitochondrial function, apoptosis, and necrosis in prostate cancer cells were investigated using 2D monolayer and 3D sphere culture systems. Cytotoxicity and cell cycle monitoring showed that butein treatment decreased cell viability and increased peaks of sub-G0/G1 and G2/M phases analyzed by flow cytometry. These changes were observed with a concurrent induction of DNA damage, apoptosis, and necrosis. Although 3D spheres treated with butein showed decreased cell viability, they were slightly more resistant than cells in 2D cultures. This phenomenon was accompanied by an increase in mediators of apoptosis and necrosis. Monitoring changes of apoptosis-related proteins via Western blot showed that butein decreased caspase-3, PARP, and Bcl-2, but increased Bax. Meanwhile, butein increased levels of p-receptor interacting serine/threonine–protein kinase 3 (p-RIP3) and p-mixed lineage kinase domain-like kinase (p-MLKL) known to be mediators of necrosis. Overall, our data suggest that butein can induce apoptosis and necrosis of prostate cancer cells by regulating pro- and anti-apoptotic proteins via ROS. Thus, butein might be a potential agent for treating prostate cancer.